ANALISIS PROSES PENGINTEGRASIAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN MATEMATIKA KELAS X ILMU ALAMSMA NEGERI 1 SURAKARTA TAHUN AJARAN 2013/2014 - RZ, Zara Mertiana; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purposes of this research were to: (1) describe the process of integrating the characteristic values of disciplinary, creative, critical thinking, inquiring, and thorough in learning mathematics at the tenth of science class SMA Negeri 1 Surakarta, and (2) describe the studentsâ opinion of the tenth of science class SMA Negeri 1 Surakarta about the integration of the characteristic values of disciplinary, creative, critical thinking, inquiring, and thorough in learning mathematics. Qualitative research was applied in this research. The subject of the research are students and a mathematics teacher of the tenth grade of Â SMA Negeri 1 Surakarta. The source of data was taken from informants (teacher and students), documentation (lesson plan), and learning activity. Data collection was taken by using interview, observation, and documentation. Data validity used the source of triangulation. Data analysis used Miles and Hubermanâs concept that are data collection, data reduction, presenting the data, and drawing the conclusion. The result of the research showed as follows. (1) Integrating character education of discipline, teacher did it implicitly (being a model) and explicitly (giving an urge). To integrate the critical character, teacher associates learning with daily life and guiding students analyse the information obtained or given to the students. Creative character done by the teacher in integrating for learning mathematics was to developed active classroom and informed with gave the opportunity for students to express their ideas in solving problems of mathematics questions. The integration of inquiring character in learning mathematics was not visible. To integrate thorough character, teacher planted thorough character by giving the test and urging the students to recheck the result of their works, listen carefully to what the teacher had said. (2) According to studentsâ opinion, teacher had planted the character of disciplinary, creative, critical thinking, inquiring, and thorough. However, there was no explanation about the character of inquiring because the test given was the standard questions so that it cannot encourage students to have inquiry.Keywords: Process analysis, character education, learning mathematics